Primary and revision efficacy of cross-wired metallic stents for endoscopic bilateral stent-in-stent placement in malignant hilar biliary strictures - Lee, T. H.; Moon, J. H.; Kim, J. H.; Park, D. H.; Lee, S. S.; Choi, H. J.; Cho, Y. D.; Park, S. H.; Kim, S. J. (Endoscopy, 2013)
Background and study aims: Endoscopic bilateral drainage for inoperable malignant hilar biliary strictures (HBS) using metal stents is considered to be technically difficult. Furthermore, endoscopic revision of bilateral stenting after occlusion can be challenging. This study was performed to evaluate the long-term efficacy of endoscopic bilateral stent-in-stent placement of cross-wired metallic stents in high-grade malignant HBS and planned endoscopic bilateral revision. Patients and methods: A total of 84 patients with inoperable high-grade malignant HBS were enrolled from three academic tertiary referral centers. Two cross-wired metal stents were inserted using a bilateral stent-in-stent placement method. Bilateral endoscopic revision was also performed during follow-up using either identical metal stents or plastic stents. The main outcome measurements were technical and functional success, complications, stent patency, and endoscopic revision efficacy. Results: The technical and clinical success rates of endoscopic bilateral stent-in-stent placement of cross-wired metallic stents were 95.2 % (80 /84) and 92.9 % (78 /84), respectively. Median patency (range) and survival were 238 days (10 – 429) and 256 days (10 – 1130), respectively. Obstruction of primary bilateral stents occurred in 30.8 % (24 /78) of patients with functionally successful stent placement. The technical and clinical success rates of planned bilateral endoscopic revision for occluded stents were 83.3 % (20 /24) and 79.2 % (19 /24), respectively. For revision, bilateral metallic stents were placed in 11 patients (55.0 %); the remaining patients received plastic stents. Conclusions: Palliative endoscopic bilateral stent-in-stent placement of cross-wired metallic stents was effective in patients with inoperable HBS. Revision endoscopic bilateral stenting may be feasible and successful in cases where the primary deployed metal stents are occluded.